2017
DOI: 10.1038/ejcn.2016.274
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dietary exposure to branched chain amino acids impairs glucose disposal in vegans but not in omnivores

Abstract: Negative impact of increased BCAA intake on IS was only detected in vegans, that is, subjects with low basal amino acids/BCAA intake, which appear to be unable to induce sufficient compensatory changes within AT and SM on a BCAA challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Finally, animal protein could have a different biodisponibility or kinetics that could predispose to IR. A small study reported that vegan, who consumed less BCAAs than omnivores at baseline, had a significant decrease in insulin sensitivity after three months of BCAA supplementation [26]. Another study found a switch to fish and plant-based protein versus meat lowered plasma BCAAs in a small sample of mainly overweight individuals [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, animal protein could have a different biodisponibility or kinetics that could predispose to IR. A small study reported that vegan, who consumed less BCAAs than omnivores at baseline, had a significant decrease in insulin sensitivity after three months of BCAA supplementation [26]. Another study found a switch to fish and plant-based protein versus meat lowered plasma BCAAs in a small sample of mainly overweight individuals [58].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in plasma BCAA levels according to dietary profiles and dietary protein intakes have been investigated. While higher BCAA intakes have been related to plasma BCAA levels in some studies [16,26], others found no or an inverse association between these two factors [27,28,29]. One possible explanation for this discrepancy may be related to the source of protein, either animal or vegetal [4].…”
Section: Introductionmentioning
confidence: 99%
“…Medical records of the out-patient department at a tertiary clinical nutrition center (University Hospital Kralovske Vinohrady, Prague, Czech Republic) were used for the present study. Data of vegan adults, who attended medical check-ups between 2012 and 2019, and volunteers from previous studies [9,10] of the department, who self-identified themselves as vegans (exclusive plant-based diet) were analyzed (n = 151). Non-vegan healthy volunteers, who were recruited for previous research projects of the department (Czech Rep. Ministry of Health grants 14,416 and 18-01-00040; Charles University grant 1,280,218), were used as controls subjects.…”
Section: Study Populationmentioning
confidence: 99%
“…Thus, the beneficial effect of plant proteins on cardiovascular health may not be assigned to a specific amino acid but rather to more complex associations of the amino acids or other substances tightly associated with those proteins. Experiments in rodents and randomized controlled trials have tested the effect of specific amino acids, or associations between two amino acids [12][13][14][15][16][17], on cardiovascular risk factors, lending credence to the possible beneficial or adverse effect of some amino acids, but the data provide no information about associations with amino acids categorized by protein sources.…”
Section: Introductionmentioning
confidence: 99%